Ethnoscience in Indonesia and It’s Implication to Environmental Education: A Systematic Literature Review - Susanti Murwitaningsih; Maesaroh Maesaroh (Postgraduate, University of Mataram, 2023)
Cultural diversity and knowledge are valuable resources for expanding the concept of ethnoscience. Indonesia, with thousands of islands, is the wisdom of local communities in agriculture, the environment, traditional medicine, food, clothing, entertainment, human contact with nature, and other fields. This publication includes descriptive data from ethnoscience research in science learning in Indonesia and its significance using the SLR method. In Indonesia, ethnoscience research trends in learning are dominated primarily by research and development with research groups in the form of: integration of local knowledge in the curriculum, use of technology in ethnoscience learning, ethnoscience-based environmental education, and development of ethnoscience-based contextual learning materials.